Penguatan Inovasi Program Sekolah Preneur Inklusif - Darwin, Khadijah; Sirajuddin; Rajab, Abd.; Resmi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The Inclusive Entrepreneur School Program is an innovative approach to education that integrates entrepreneurial values into an inclusive education system to develop independent, creative, and collaborative students. This community service activity aimed to disseminate this concept to all school elements at the Sitti Zaenab Tamzil Foundation in Pangkep Regency, South Sulawesi. The activity took place on August 1, 2025, and was attended by 124 participants, including teachers, parents, and students. The activity method included participatory planning, implementation through interactive presentations and group discussions, and evaluation based on participant feedback and reflection. The results of the activity indicated a positive response from all participants, with the emergence of collaborative initiatives to develop school-based entrepreneurship activities. This dissemination provided an initial contribution to building synergy among school stakeholders and served as an important stepping stone towards the implementation of inclusive and sustainable contextual education.